PENERAPAN MODEL TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS V MI MUHAMMADIYAH CECE - Sira Natasha; Aminullah; Wulandari (STKIP Subang, 2026)
This study was motivated by the low learning outcomes of fifth-grade students in the Pancasila Education subject at MI Muhammadiyah Cece, which were caused by the dominance of conventional, teacher-centered teaching methods that left students passive and lacking a deep understanding of the material. This research aimed to describe the implementation of the Talking Stick learning model and to determine the extent to which the model could improve students’ learning outcomes on the topic of rights and obligations. This study employed a Classroom Action Research (CAR) design following the Kemmis and Mc Taggart model, consisting of the stages of planning, action, observation, and reflection, carried out over two cycles with four meetings. The subjects were 21 fifth-grade students, comprising 12 female and 9 male students. Data were collected through multiple-choice achievement tests, observation sheets, and documentation, and were analyzed descriptively using mean scores and percentages. The results showed that the percentage of students who achieved the minimum learning completion criterion (KKTP ≥ 75) increased from 9.52% in the pre-action stage to 38.10% in Cycle I, and further increased to 95.23% in Cycle II. Student engagement and teacher performance also improved substantially between cycles. These findings indicate that the Talking Stick learning model is effective in improving the learning outcomes of fifth-grade students in Pancasila Education at MI Muhammadiyah Cece.